Relatively favorable outcome after allogeneic stem cell transplantation for BCR‐ABL1‐positive AML: A survey from the acute leukemia working party of the European Society for blood and marrow transplantation (EBMT). Issue 1 (31st October 2017) - Lazarevic, Vladimir Lj; Labopin, Myriam; Depei, Wu; Yakoub‐Agha, Ibrahim; Huynh, Anne; Ljungman, Per; Schaap, Nicolaas; Cornelissen, Jan J.; Maillard, Natacha; Pioltelli, Pietro; Gedde‐Dahl, Tobias; Lenhoff, Stig; et al.
Abstract: The aim of the study was to assess the role of allogeneic stem cell transplantation (SCT) in patients diagnosed with BCR‐ABL1 ‐positive acute myeloid leukemia (AML). Fifty‐seven patients (median age, 48 years, range: 19‐67) with BCR‐ABL1 positive AML undergoing SCT were identified. The majority of the patients (70%) received a TKI before the transplant. At SCT 48 patients were in CR (45 in CR1), while 9 patients were transplanted in a more advanced stage of the disease. MRD was negative ( BCR‐ABL1/ABL  < 10 4 ) at time of SCT in 36.1% (14/40). After SCT, 16 (61.5%) out of 26 patients with MRD positive at transplantation reached MRD negativity. After a median follow‐up of 6.3 years (0.7–14.2), NRM, RI, LFS, OS, and GRFS at 5 years were 18.1%, 37%, 44.2%, 53.8%, and 32.1%, respectively. The cumulative incidence of acute GvHD grade II‐IV was 16.4%, incidence of chronic GvHD 24.9%, and of extensive cGvHD 21.4%, respectively. In patients who received SCT in CR1, 5‐yr NRM, RI, LFS, OS, and GRFS were 15.9%, 36.4%, 46.5%, 59.4%, and 34.9%, respectively. Univariate analysis showed that age (<50 vs. ≥50 years) was associated with RI (5‐yr: 22.7 vs. 50%), LFS (5‐yr: 61.9 vs. 31.8%), and GRFS (5‐yr: 52.4 vs. 18.2%), whereas MRD‐negative status before SCT was associated with an improved GRFS (38.9 vs. 16.7%). We conclude that the outcome of patients <50 years of age with BCR‐ABL1‐ positive AML receiving allogeneic SCT in CR is relatively favorable, possibly reflecting the beneficial effect of the use of TKI.